Does Security Concern, Perceived Enjoyment and Government Support Affect Fintech Adoption? Focused on Bank Users - Zaiton Osman; Izyanti Awang Razli; Phang Ing @ Grace (Sarawak Research Society, 2021)
Today, following the globalization of business and systems, together with advancement of technology, has revolutionized the way users access their finances. A new mean of banking services which use innovative information and automation technology or also known as fintech has been used widely. In line with this, there is a pressing need to understand the factors that affecting bank user’s acceptance on fintech services. Using Technology Acceptance Model (TAM), this study conducted an analysis on three variables (security concerns, perceived enjoyment and government support) and age as a moderating variable that may influence the acceptance of fintech services. Using quantitative survey, 500 usable questionnaires were collected. The results indicate that security concerns and government support significantly influence the intention to adopt fintech while perceived enjoyment is not. Age did not moderate the relationship in all three variables. The research contributes to a review of fintech service adoption in Malaysia, with the aim of examining users' intentions to adopt fintech services.